2021
DOI: 10.3390/f12070956
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and Micronutrient Contents in Soils of a Chronosequence of Naturally Regenerated Birch Stands on Abandoned Agricultural Lands in Central Poland

Abstract: Abandoned agricultural lands in Central and Northern Europe undergo a quite rapid secondary succession of woody species, especially silver birch (Betula pendula Roth.) as a pioneer tree species. Such a process is desirable both from natural and economic point of views, as afforestation involves a change to the entire ecosystem and, in particular, the transformation of anthropogenic habitats typical for agriculture into habitats similar to a natural forest. In the present study, we report the chemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Coal mining areas are highly susceptible to heavy metal pollution released from coal gangue (Liu et al, 2018), and we analyzed both total soil elements and effective state elements at different soil depths after long-term woody plant restoration. We found that the soil effective state elements decreased signi cantly, mainly at the 50-100 cm depth after restoration of the four woody plant species, in agreement with a previous report (Gawęda et al, 2021), and that plant roots developed more strongly at deeper depths and promoted the uptake of deep soil nutrients and metals. By contrast, the plant-free control area showed a sharp decrease at 10 cm depth, implying that effective elements are subject to interference by external factors, such as sunlight, weathering, and rainfall (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Coal mining areas are highly susceptible to heavy metal pollution released from coal gangue (Liu et al, 2018), and we analyzed both total soil elements and effective state elements at different soil depths after long-term woody plant restoration. We found that the soil effective state elements decreased signi cantly, mainly at the 50-100 cm depth after restoration of the four woody plant species, in agreement with a previous report (Gawęda et al, 2021), and that plant roots developed more strongly at deeper depths and promoted the uptake of deep soil nutrients and metals. By contrast, the plant-free control area showed a sharp decrease at 10 cm depth, implying that effective elements are subject to interference by external factors, such as sunlight, weathering, and rainfall (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Last research has shown that B. pendula has developed traits, which help to survive [ 48 ]. For this reason, it is used as a remedial plant [ 49 51 ], which makes it more and more widespread and conducive to use in biomonitoring [ 1 , 51 , 52 ]. Therefore, it becomes important to determine the influence of the soil species, as well as other physicochemical properties of the soil on the possibility of accumulation of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Daugaviete et al (2003) and Aosaar et al (2016) reported positive effects of birch trees on soil N during the first few years after afforestation. Additionally, Uri et al (2012) and Gawęda et al (2014) observed increasing contents of the major nutrients in soils under birch chronosequences. Birch biomass is generally moderately abundant in nutrients; however, their concentrations are strongly controlled by their bioavailability (Daugaviete et al 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Fresh silver birch biomass is moderately abundant in P, with the highest contents being reported in leaves and the lowest in wood (Novák et al 2017;Rustowska 2022). A major pool of the element is allocated in the aboveground biomass, in the branches and foliage (Ukonmaanaho et al 2008;Gawęda et al 2014;Novák et al 2017). The silver birch litterfall in the studied stands contained 1.05-1.68 g kg −1 P, and leaves were the richest source of the element among the litterfall fractions, followed by flowers and seeds (Table 4, Supplementary material).…”
Section: Litterfall Chemistrymentioning
confidence: 99%
See 1 more Smart Citation